PROBLEM OF ANTIBIOTIC USE AND ANTIMICROBIAL RESISTANCE IN INDONESIA: ARE WE REALLY MAKING PROGRESS? - Hadi, Usman; Kuntaman, Kuntaman; Qiptiyah, Mariyatul; Paraton, Hari (Institute of Topical Disease, 2013)
Background: Based on the results Antimicrobial Resistance in Indonesia: prevalence and prevention-study (AMRIN-study), the Ministry of Health of Indonesia in 2005 began a program antibiotic resistance control (PPRA) in some government hospitals, and is currently developing to all government teaching hospitals in Indonesia. Aim: The core activities of the PPRA are to implement standardized surveillance emergence of antibiotic resistant bacteria, and the surveillance of antibiotic use in terms of quantity and quality. Method: Our research in the years 2003 showed the proportion of antibiotic use 84% of patients in a hospital. The use of inappropriate antibiotics was very high, 42% no indication. Result: In 2012 the results of surveillance showed decline of inappropriate use of antibiotic, but prevalence extended-spectrum b-lactamase (ESBL)-producing K.pneumoniae (58%), and E.coli (52%) andmethicillin-resistant S.aures (MRSA) (24%) were increasing. Conclusion: It was needed to implement the most appropriate programs to prevent the growth and development of bacteria resistant to antibiotics.